Avaliação em laboratório do comportamento de camadas asfálticas reforçadas com geossintéticos - Leonardo Lacerda Fonseca (2015)
The performance of a pavement structure is a function not only of the materials constituting the layers, but also the way in which interaction occurs between them. It is expected that the structural layer present monolithic behavior, resulting in best stress transfer. The pavement is designed and built in order to perform their duties in a given period, as well, there will be a moment that life will be won and will then be necessary interventions to restore the appropriate conditions, which fit techniques for using geosynthetic materials as a reinforcement element in the layers of asphalt mixture. Considering the need for pavement restoration, the work aimed to laboratory evaluation of behavior and reinforcement systems performance with use of a geogrid and geotextile, being varied the lead paint rates and types of used emulsions, RR IC and RR 2C. Other studies point out that the adhesion between the geosynthetic and the asphalt layers interfere significantly in the success of the reinforcement system. When paving the service that provides the adhesion between the layers is lead paint, which is applied an optimum amount for each case, considering that lower applications rates may result in loss of adhesion and rates higher than ideal, can promote creating a film residue bituminous material that can generate shear strength falls. That said, it was carried out direct shear tests on systems with and without geosynthetics. With the results obtained it was concluded that the inclusion of geotextile or geogrid significantly reduces the shear strength between the layers, however, in case there are appropriate conditions of quantity and type of asphalt emulsion applied in connection paint allow the use of satisfactorily reinforcement systems. The direct shear tests alone assess the adhesion behavior between the layers and these and geosynthetics, however, in reality the internal forces generate different requests to this, so that the systems should have their mechanical performance also investigated. The performances of the systems were evaluated for tensile strength in bending, certain beams. The results showed that the use of geosynthetic increases the tensile strength and the bending performance is a function of the type of geosynthetic material, the viscosity of the emulsion and its application rate.